Conservative management of cecal diverticulitis mimicking acute appendicitis in a pregnant woman - Choi, Won Ku; Song, Yun Kyung; Kim, Sun Young; Rheu, Chul Hee; Jeong, Young Ju; Chae, Hee Suk (Korean journal of obstetrics & gynecology, 2012)
A 24-year-old pregnant woman was referred for further evaluation and treatment of the right lower quadrant pain at 19+1 weeks gestational age. The patient was diagnosed to be acute appendicitis and underwent laparoscopic surgery. However, an inflamed solitary cecal diverticulum was found during surgery. After a routine appendectomy, cecal diverticulitis was conservatively treated with postoperative antibiotics without signs of peritonitis. To date, most of the non-pregnant women with cecal diverticulitis have been managed surgically. Our case indicates that a pregnant patient with cecal diverticulitis could be managed medically during pregnancy. KCI Citation Count: 0